Comparative population dynamics of two sympatric Palaemon shrimps (Palaemon adspersus Rathke, 1836 and Palaemon elegans Rathke, 1836) from the Southeast Caspian Sea - Vejan, Alti; Patimar, Rahman; Jafaryan, Hojjatallah; Gholizadeh, Mohammad; Adineh, Hossein; Aghilinezhad, Seyyed Mostafa (Frontiers in Marine Science, 2022)
This study provides comparative information about population dynamics for the Palaemon adspersus and Palaemon elegans shrimps on the southeastern coast of the Caspian Sea. Specimens were collected on a monthly basis between April 2019 and May 2020. A total of 9643 specimens (8478 P. adspersus and 1165 P. elegans) were captured and examined. The highest abundance of both shrimps was observed in autumn. The male P. elegans ranged between 16.80 mm and 61.99 mm in total length and the females between 16.80 mm and 61.99 mm. The total length for male and female P. adspersus ranged from 21.46 to 69.29 mm and 18.24 to75.46 mm, respectively. The mean (±SD) total length for males and females of P. elegans was 33.65±4.12 and 40.81±6.59, whereas that of P. adspersus was 48.41±6.27 for males and 54.68±9.90 for females. Based on the b-value of LWR, the growth type of P. adspersus is positive allometric. Likewise, the relationships of female and pooled sexes P. elegans was a positive allometric, while that of male P. elegans was negatively allometric. Estimation of the VBGF parameters resulted as TL∞=71.93 mm, K=0.72 y-1 and t0=-0.176 for males, and TL∞=78.23 mm, K=0.64 y-1 and t0=-0.194 for females of P. adspersus, while for P. elegans as TL∞=56.13 mm, K=0.91 y-1 and t0=-0.147 for males and TL∞=65.63 mm, K=0.87 y-1, and t0=-0.148 for females. The size-frequency analysis showed that both shrimps were made up of two age groups. The recruitment pattern of the shrimps was continuous with unimodal pulse for both males and females and showed that P. adspersus is mainly recruited during the autumn and early winter, while P. elegans during mid-summer and early autumn. The Estimated maximum age was 3.35/year for males and 2.66/year for females of P. adspersus and 3.78/year for males and 3.33/year for females of P. elegans. Therefore, in this case, P. elegans shrimp is more sensitive to death than P. adspersus. The findings point to the underlying notable differentiation of the growth of the shrimps governing processes of population dynamics. We assume that these differences result from the contrasting life-history strategies of these two Palaemon shrimps.